Dampak Kerajaan Siak Sri Indrapura terhadap Kebudayaan Melayu di Riau - Irmayana, Irmayana; Batu Bara, Farhana Aziz; Siregar, Yusra Dewi (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2024)
This research aims to analyze the impact of the Siak Sri Indrapura Kingdom on the development of Malay culture in Riau. The Siak Sri Indrapura Kingdom, established in the 18th century, played a crucial role in shaping the Malay cultural identity in the region. This study employs a historical and qualitative approach, gathering data from various historical sources, literature, and interviews with Malay cultural experts. The findings reveal that the Siak Sri Indrapura Kingdom significantly contributed to the dissemination of Islamic values, customs, arts, and the Malay language in Riau. This influence not only strengthened the local cultural identity but also shaped social and political dynamics that are still evident today. This research is expected to provide a deeper understanding of the cultural heritage of the Siak Sri Indrapura Kingdom and its relevance in the context of contemporary Malay culture in Riau.